Implementasi Kebijakan Disiplin Pegawai Negeri Sipil Di Dinas Pendidikan Kota Surakarta - Fina Nur Cahyani; Aloysius Rengga; Aufarul Marom (Journal of Public Policy and Management Review, 2016)
The aim of this study to analyze enforcement of disciplinary rules and implementation of civil service disciplinary sanction in Dinas Pendidikan Kota Surakarta based on Government Regulation No. 53 Tahun 2010 about discipline of civil servants. The type of this research is qualitative descriptive. Technique of data collecting used direct observation to the main object, held interview with informant to get comprehensive information by asking some question about the main problem. Study of literature by reading books, magazine, newspaper, documents, legislation and other information that relevant with the object of research and supported by secondary data. The result of research showed that enforcement of disciplinary rules in Dinas Pendidikan Kota Surakarta is still not optimal whereas the application of disciplinary sanctions in accordance with the rules of discipline of civil servants is Government Regulation No. 53 Tahun 2010.